Satan Shoes or Satan Speech? Balancing Trademark and First Amendment Rights in the Altered Authentic Goods Context - Seminara, Ann (The Columbia Journal of Law & the Arts, 2023)
In March 2021, art collective MSCHF released 666 pairs of radically altered Nike Air Max 97 sneakers on its website, christening them “Satan Shoes.” The sneakers were updated from their original form to include a pentagram charm hanging from the laces and a citation to “Luke 10:18” printed on the mudguards. MSCHF employees allegedly mixed their own blood with red ink and injected the combination into the shoes’ midsoles. A small black loop of fabric featuring an upside-down cross extended from the shoes’ tongues, and each shoe was individually numbered out of 666 above the heel. The Satan Shoes—arguably more artistic expression than consumer good after undergoing these devilish alterations—invite the question: Do artists who redesign authentic goods bearing famous trademarks and re-sell those goods to consumers violate the Trademark Act of 1946 (“the Lanham Act”)? If so, can they assert a First Amendment defense? “Internet mischief maker” Gabriel Whaley founded MSCHF in 2016 as “a creative studio that makes internet to tell stories,” and the collective’s work has been compared to the work of prolific artists like Banksy, Warhol, and Duchamp. Every two weeks, MSCHF “drops” new art on its website. CNN referred to the collective as “the master of releasing products that nobody really needs, but everyone absolutely wants.” Previous drops have included works like the Cuss Collar, a dog collar that swears whenever the dog wearing it barks and a weekly newsletter filled with “unhinged” email chains called Boomer Email. Many of MSCHF’s drops make pointed political and social commentary. For instance, MSCHF offers a Guns to Swords program that promises to buy people’s guns, melt them down into swords, and send the swords back to the former-guns’ owners. In its Medical Bill Art drop, MSCHF made paintings out of three medical bills, sold them for $73,000, and used the funds to erase the bill recipients’ medical debt. MSCHF placed its Satan Shoes for sale on its website in late March, 2021 as part of its forty-third drop. Crucially, Nike was not involved in the Satan Shoes’ design, modification, or sale and did not endorse the Satan Shoes in any way. MSCHF created the Satan Shoes in collaboration with Lil Nas X, a music artist who released the song “Montero (Call Me By Your Name)” alongside a music video in which Lil Nas dances seductively with the devil. Lil Nas X described his work as responding to LGBTQ repression. In the media, outcry over the music video compounded with outcry over the Satan Shoes’ release, particularly on Twitter. Some social media users—ostensibly confused as to the Satan Shoes’ affiliation—insisted that they would never purchase Nike products again, with one suggesting that Nike should be “cancelled” over the Satan Shoes design and release. Whether such comments were posted in good faith or simply to fan the controversy’s flames cannot be confirmed. On March 26, 2021, 665 pairs of the Satan Shoes sold online for $1,018 per pair within one minute of their release. Nike sued MSCHF in the Eastern District of New York (EDNY) on March 29, alleging trademark infringement, false designation of origin, unfair competition, and trademark dilution under the Lanham Act, as well as common law trademark infringement and unfair competition. By April 7, the parties had settled, but not before Nike secured a temporary restraining order against MSCHF. MSCHF does not fit the image of a typical counterfeiter. The Satan Shoes are not counterfeits or knockoffs and MSCHF is not trying to pass them off as authentic Nikes because they are authentic Nikes. MSCHF describes itself as an “art collective,” and sometimes refers to its work as “performance art.” In other words, MSCHF had a unique opportunity to argue that in creating the Satan Shoes it sought to create works of art that comment upon Nike and collaboration culture rather than a product that would freeride off of Nike’s goodwill and reputation. That is exactly what MSCHF argued before it settled. Whether the Satan Shoes are more akin to Medical Bill Art’s impactful artistic commentary or more like the Cuss Collar, an entertaining consumer product, is an intellectually valuable debate not only for cultural critics but also for the legal world. This Note will argue that authentic goods that are altered post-sale and resold primarily as works of artistic expression to sophisticated consumers should be protected by the First Amendment. In doing so, this Note will offer courts a framework for analyzing whether an altered authentic good should qualify for a First Amendment defense by determining whether the good functions more like a competing consumer product or a work of artistic expression in the marketplace. Part I of this Note will provide an overview of the relevant trademark law. Part II will discuss the legal problems posed by cases involving modified authentic goods that function like art, and the lack of relevant defenses for trademark use in that context. Part III proposes considerations for courts seeking to balance trademark owners’ rights with the rights of the public to sell modified authentic goods as artistic expression. Part III also provides business considerations for those seeking to modify and resell authentic goods.